Physiological Stress Responses Associated with Microplastic Ingestion in the Benthic Flatfish Bothus podas - Amanda Cohen-Sánchez; Montserrat Compa; Jessica Lombardo; Maria Magdalena Quetglas-Llabrés; Maria del Mar Ribas-Taberner; Manuel Jiménez-García; Silvia Tejada; Antoni Sureda (Toxics)
Bothus podas (wide-eyed flounder) is a benthic flatfish likely exposed to microplastic (MP) pollution. We investigated MP ingestion and associated physiological effects in wild B. podas collected from Mallorca (Balearic Islands), Spain. Markers of oxidative stress, detoxification, and immunity were quantified in intestinal, hepatic, and splenic tissues. MPs were observed in the gastrointestinal tracts of 87.5% of the 24 specimens analyzed, with an average of 3.8 ± 0.6 items per fish. Fiber-type MPs predominated in both the gastrointestinal tract (69.6%) and sediment samples (97%). Additionally, micro-Fourier transform infrared spectroscopy analysis confirmed that the majority of ingested MPs were composed of polyethylene, polypropylene, and polyester. Fish were categorized into low (<3 items) and high (≥3 items) MP groups based on the median number of plastic items found in the gastrointestinal tract to assess sublethal impacts. In the gut, high-MP fish exhibited significantly elevated activities of detoxification enzymes: ethoxyresorufin-O-deethylase (phase I) and glutathione s-transferase (phase II), along with increased antioxidant enzyme superoxide dismutase and inflammatory myeloperoxidase. Gut catalase and malondialdehyde (MDA) were not significantly different between groups. In liver tissues, no biomarkers differed significantly with MP exposure. In the spleen, lysozyme and alkaline phosphatase activities were significantly higher in high-MP fish, while splenic MDA remained unchanged. These results indicate that gastrointestinal MP exposure triggers local oxidative stress responses and systemic immune activation in B. podas. Overall, ingestion of environmentally relevant MP levels elicited detoxification and inflammatory responses without significant increases in MDA, an indicator of oxidative damage, highlighting the physiological stress imposed by plastic pollution on benthic fish.